Essays on foreign acquisition, multiproduct firms and international trade: evidence from China - Zhang, Rhea Yuzhu (2020)
Based upon the context of China getting integrated into the global economy, this thesis explores three distinct research questions concerning the effects of foreign direct investment (FDI) on firms' export and import profiles as well as the relationship between working capital management and export participation.